Integrative transcriptome analysis revealed the pathogenic molecular basis of Rhizoctonia solani AG-3 TB at three progressive stages of infection - Li, Xinchun; An, Mengnan; Xu, Chuantao; Jiang, Lianqiang; Yan, Fangfang; Yang, Yang; Zhang, Chong; Wu, Yuanhua (Frontiers in Microbiology, 2022)
Rhizoctonia solani has a broad host range and results in significant losses in agricultural production. Here, an integrated transcriptomic analysis was performed to reveal the critical genes responsible for the pathogenesis of R. solani AG-3 TB on Nicotiana tabacum at different infection stages. The results showed that various differential expressed genes (DEGs) were enriched in fatty acid metabolism, amino sugar, carbon metabolism and cellular carbohydrate biosynthetic process at the early (6-12 hpi), middle (24-36 hpi) and late stage (48-72 hpi) of infection. Specifically, several critical genes such as shikimate kinase that were involved in the biosynthesis of an important fungal toxin, phenylacetic acid (PAA) showed markedly increase at 24 hpi. Additionally, the genes expression levels of carbohydrate-active enzymes (CAZymes) and cell wall degrading enzymes (CWDEs) were significantly increased at the late infection stage. Furthermore, we identified 807 potential secreted proteins and 78 small cysteine-rich proteins, which may function as fungal effectors and involved in the pathogenicity. These results provide valuable insights into critical and potential genes as well as the pathways involved in the pathogenesis of R. solani AG-3 TB.